2016
DOI: 10.1111/1365-2478.12405
|View full text |Cite
|
Sign up to set email alerts
|

Are changes in time‐lapse seismic data due to fluid substitution or rock dissolution? A CO2 sequestration feasibility study at the Pohokura Field, New Zealand

Abstract: Seismic methods are commonly used to monitor the subsurface when carbon dioxide (CO2) is injected into a reservoir. Besides fluid saturation and pressure changes, CO2–water mixtures may cause rock alteration. In this petrophysical study, we compare the elastic property changes due to fluid replacement and those due to mineral dissolution for carbonate‐cemented sandstones at the Pohokura Field, New Zealand. We quantify the effects of fluid substitution from fully brine to fully supercritical CO2 saturation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Combined with image analysis (scanning electron microscope and thin section), previous studies have shown that the magnitude of these changes is strongly dependent on the initial pore structure and the microstructural relationship between cement and framework grains by affecting the reactive surface area under similar reservoir conditions (Hangx et al, ; Rinehart, Dewers, et al, ; Vanorio et al, ; Vialle & Vanorio, ). Furthermore, modeling suggests that the underlying mechanism of mechanical alteration is due to the volume reduction of grain contact cement (Sim & Adam, ; Zheng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Combined with image analysis (scanning electron microscope and thin section), previous studies have shown that the magnitude of these changes is strongly dependent on the initial pore structure and the microstructural relationship between cement and framework grains by affecting the reactive surface area under similar reservoir conditions (Hangx et al, ; Rinehart, Dewers, et al, ; Vanorio et al, ; Vialle & Vanorio, ). Furthermore, modeling suggests that the underlying mechanism of mechanical alteration is due to the volume reduction of grain contact cement (Sim & Adam, ; Zheng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A core extracted 2 years post‐injection showed evidence of secondary carbonate mineral precipitation in the form of ankerite throughout the rock vesicles [ McGrail et al , ]. Reservoir characterization and monitoring of the CO 2 plume in the field is required to understand changes in the rock physical properties due to rock‐fluid interactions [ Sullivan et al , ; Khatiwada et al , ; Sim and Adam , ].…”
Section: Introductionmentioning
confidence: 99%
“…These surveys often rely on the assumption that the velocity change is only caused by fluid substitution. However, CO2$_2$ can react with or dissolve the host rock, causing changes in the seismic velocity of the bulk rock (Lumley, 2010; Sim & Adam, 2016).…”
Section: Introductionmentioning
confidence: 99%